Acral Lentiginous Melanoma: A United States Multi-Center Substage Survival Analysis. (7th November 2021) - Kolla, Avani M.; Vitiello, Gerardo A.; Friedman, Erica B.; Sun, James; Potdar, Aishwarya; Daou, Hala; Farrow, Norma E.; Farley, Clara R.; Vetto, John T.; Han, Dale; Tariq, Marvi; Beasley, Georgia M; et al.
Background: Acral lentiginous melanoma is associated with worse survival than other subtypes of melanoma. Understanding prognostic factors for survival and recurrence can help better inform follow-up care. Objectives: To analyze the clinicopathologic features, melanoma-specific survival, and recurrence-free survival by substage in a large, multi-institutional cohort of primary acral lentiginous melanoma patients. Methods: Retrospective review of the United States Melanoma Consortium database, a multi-center prospectively collected database of acral lentiginous melanoma patients treated between January 2000 and December 2017. Results: Of the 433 primary acral lentiginous melanoma patients identified (median [range] age: 66 [8–97] years; 53% female, 83% white), 66% presented with stage 0–2 disease and the median time of follow-up for the 392 patients included in the survival analysis was 32.5 months (range: 0–259). The 5-year melanoma-specific survivals by stage were 0 = 100%, I = 93.8%, II = 76.2%, III = 63.4%, IIIA = 80.8%, and IV = 0%. Thicker Breslow depth ((HR) = 1.13; 95% CI = 1.05–1.21; P < .001)) and positive nodal status ((HR) = 1.79; 95% CI = 1.00–3.22; P = .050)) were independent prognostic factors for melanoma-specific survival. Breslow depth ((HR = 1.13; 95% CI = 1.07–1.20; P < .001), and positive nodal status (HR = 2.12; 95% CI = 1.38–3.80; P = .001) were also prognostic factors for recurrence-free survival. Conclusion: In this cohort of patients, acral lentiginous melanoma was associated with poor outcomes even in early stage disease, consistent with prior reports. Stage IIB and IIC disease were associated with particularly low melanoma-specific and recurrence-free survival. This suggests that studies investigating adjuvant therapies in stage II patients may be especially valuable in acral lentiginous melanoma patients.